Dynamic Stability Improvement of Power System with VSC-HVDC Transmission - Vasudevan, R; Ramalakshmi, S (International Journal of Engineering and Technology, 2018)
A new management approach for the reactive-power injections of Voltage supply Converters in High Voltage DC (VSC-HVDC) multi-terminal Systems to enhance grid transient stability. A reactive-power supplementary signal is provided for each convertor. Its worth is proportional to the frequency deviation of its consequent AC bus with admiration to the weighed-average frequency of the multiterminal system stations. The hope is to extend (decrease) the magnetism torsion of generators close to those terminals during which the frequency is superior to (below) the weighed-average frequency used. The AC frequency for all VSC stations is ever more accessible regionally for synchronization functions and will be utilized by a central controller. Simulations are allotted victimization PSS/E and therefore the outcome have revealed that transient stability is enlarged victimization this approach. Since this approach uses world capability of all VSC stations, the collision of the communication delays has been analyzed, concluding that the depressing consequence is modest, for realistic latency values.Â